Patient perspectives on a national multidisciplinary team meeting for a rare cancer. (3rd December 2018) - Bate, Jessica; Wingrove, Jane; Donkin, Alexandra; Taylor, Rachel; Whelan, Jeremy
Abstract: Multidisciplinary team meetings (MDTM) provide a regular forum for cancer teams to convene and discuss the diagnostic and treatment aspects of patient care. For some rare cancers, MDTMs may also occur at national level to pool expertise and to ensure more consistent decision‐making. One such national MDTM exists in the UK for patients with a diagnosis of Ewing's sarcoma of the bone—the National Ewing's MDT (NEMDT). This study explored the patient perspective of this rare cancer national MDTM using focus group and survey methodology. Study participants used their experience to provide several recommendations: that their views should always inform the decision‐making process, these views should be presented by someone who has met them such as a specialist nurse, MDT recommendations should be provided to them in plain English, and tools to improve patient choice and enhance communication should be implemented. These patient‐centred recommendations will be used to improve the NEMDT but may be valid to inform quality improvement processes for other similar national panels.